Knowledge-based Intellectual Property Management for Technology Development Industry - Cheung, C.F.; Wang, W.M.; Tse, Y.L.; Ma, Ricky (Journal of Knowledge Management Practice, 2013)
Intellectual Property Management (IPM) is important for enhancing the competitiveness of organizations, especially for technology and innovation companies. A good practice of IPM not only creates value from Intellectual property (IP) assets but also improves the knowledge acquisition and retention processes. However, most of the IPM systems available in the market are information driven and mainly provide the information instead of the knowledge to support the knowledge work for managing IP. This paper presents a Knowledge-based Intellectual Property Management system (KBIPMS) which attempts to incorporate the knowledge work to support IPM based on the needs of the Technology Development industries. A prototype was developed and successfully trial implemented in a selected reference site. It also provides an important means for increasing the IP awareness of companies in Technology Development industry.
Keywords: Knowledge management; Intellectual property management; Technology development industry